1991
DOI: 10.1007/bf01296620
|View full text |Cite
|
Sign up to set email alerts
|

Health status and health care use in persons with inflammatory bowel disease

Abstract: We randomly surveyed 997 members of the Crohn's and Colitis Foundation of America with inflammatory bowel disease (320 ulcerative colitis and 671 Crohn's disease) in order to: (1) assess their health status, (2) compare members with ulcerative colitis and Crohn's disease, and (3) determine the correlates of health care use. Data collection included variables relating to physical and psychological symptoms, medication use, daily functional status, perceptions of health, and coping styles. The findings indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
93
3
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(102 citation statements)
references
References 30 publications
4
93
3
1
Order By: Relevance
“…17 CD was found to be associated with higher rates of anxiety and depression across some controlled studies, 23,24 however the relationship was often explained by the greater severity of the disease. 22,25 Research over the past decade has endeavoured to further clarify questions of clinical interest regarding the relationship between IBD and psychiatric disorders. [26][27][28] That is, (a) do psychiatric disorders occur at a higher level in IBD than base rates might project; (b) do psychiatric disorders contribute to greater risk of disease onset, and (c) do psychiatric disorders affect disease relapse or disease management.…”
Section: Relationship Of Anxiety and Depressive Disorders And Inflammmentioning
confidence: 99%
“…17 CD was found to be associated with higher rates of anxiety and depression across some controlled studies, 23,24 however the relationship was often explained by the greater severity of the disease. 22,25 Research over the past decade has endeavoured to further clarify questions of clinical interest regarding the relationship between IBD and psychiatric disorders. [26][27][28] That is, (a) do psychiatric disorders occur at a higher level in IBD than base rates might project; (b) do psychiatric disorders contribute to greater risk of disease onset, and (c) do psychiatric disorders affect disease relapse or disease management.…”
Section: Relationship Of Anxiety and Depressive Disorders And Inflammmentioning
confidence: 99%
“…steroid dosage, the number of stools), were included in the model. 41 From these studies, it is evident that risk of UC-related hospitalization increases substantially as the disease becomes more severe. Disease severity is associated not only with more hospitalizations but also with a longer length of stay (LOS) for each admission.…”
mentioning
confidence: 99%
“…In contrast, a US study reported a 28% hospitalization rate in patients with steroidrefractory UC during the first year after colectomy. 40 Drossman et al 41 directly examined the relationship between symptom severity and hospitalization, finding that a 1-point increase in symptom severity score was associated with a 0.05 increase in the number of hospitalizations during the past 2 years and 0.07 increase in the number of lifetime surgeries. The results were not significant, however, possibly because other variables that were highly correlated with symptom severity (e.g.…”
mentioning
confidence: 99%
“…In particular, the IBDQ [21]sensitively detects differences in quality of life between groups and changes over time [22], while other instruments, particularly the Rating Form of IBD Patient Concerns (RFIPC) [23], provide rich qualitative data about the concerns of particular patient groups. The RFIPC has facilitated the determination of the normal worries or concerns of people with IBD in several different populations including a community sample of members of the Crohn’s and Colitis Foundation of America [24], gastro-intestinal out-patients [23], IBD patients in several different countries [25], IBD patients with a recent history of psychosocial counselling [26]and between genders [24, 26]. …”
Section: Concerns and Stressors In Ibdmentioning
confidence: 99%